The Relationship Between The Role Of Health Workers And BPJS Participants' Satisfaction In The Outpatient Room Of Mayjen H. Thalib Hospital, Sungai Penuh City, 2025 - Ratu Balqiss; Dwi Noerjoedianto; Budi Aswin (International Journal of Health Engineering and Technology, 2026)
Quality and affordable health services are the right of every citizen, which the government strives to provide through the National Health Insurance (JKN) program organized by BPJS Kesehatan. However, participant satisfaction with health services remains a challenge, one of which is related to the role of health workers. This study aims to analyze the relationship between the normative, ideal, and factual roles of health workers with BPJS participant satisfaction in the outpatient ward of Mayjen H. Thalib Regional General Hospital. This study used an analytical observational design with a cross-sectional approach. The study population was all BPJS PBI participants in Sungai Penuh City with a sample of 106 respondents selected using systematic random sampling techniques. Data were collected through structured interviews using questionnaires and direct observation with checklists. Data analysis was carried out using univariate and bivariate methods. The results showed that the majority of respondents (64.2%) expressed dissatisfaction with the services received. Bivariate analysis showed a significant relationship between the normative role (p-value = 0.041; PR = 1.406), ideal role (p-value = 0.000; PR = 4.731), and factual role (p-value = 0.028; PR = 1.443) of health workers with BPJS participant satisfaction. Therefore, improving the quality of interpersonal interactions, empathy, and officer compliance with service standards is necessary to improve patient satisfaction and the quality of hospital services.